In situ cavitation bubble manometry reveals a lack of light-activated guard cell turgor modulation in bryophytes - Craig R. Brodersen; Tim J. Brodribb; Uri Hochberg; N. Michele Holbrook; Scott A. M. McAdam; Joseph Zailaa; Brett A. Huggett; Philippe Marmottant (Proceedings of the National Academy of Sciences, 2025)
Diversification of plant hydraulic architecture and stomatal function coincides with radical changes in the Earth’s atmosphere over the past 400 my. Due to shared stomatal anatomy with the earliest land plants, bryophyte stomatal behavior may provide insights into the evolution of stomatal function, but significant uncertainty remains due to technical limitations of measuring guard cell turgor pressure in situ. Here, we introduce a method for monitoring cell turgor pressure by nucleating microbubbles within the guard cells of intact plant tissue and then examining microbubble growth and dissolution dynamics. First, we show that maximum microbubble radius decreases with increasing pressure as the pressure of the surrounding fluid constrains its growth according to a modified version of the Epstein–Plesset equation. We then apply this method to monitor turgor pressure in dark- vs. light-acclimated guard cells across bryophyte taxa with stomata, where their role in gas-exchange remains ambiguous, and in vascular plants with well-documented light-dependent turgor modulation. Our findings show no light-activated change in turgor in bryophyte guard cells, with pressures not significantly different than neighboring epidermal cells. In contrast, vascular plants show distinct pressure modulation in response to light that drives reversible changes in stomatal aperture. Complete guard cell turgor loss had no effect on bryophyte stomatal aperture but resulted in partial or complete closure in vascular plants. These results suggest that despite conserved stomatal morphology, the sampled bryophytes lack dynamic control over guard cell turgor that is critical for sustaining photosynthesis and inhibiting desiccation.